2015
DOI: 10.1007/s00265-015-1890-4
|View full text |Cite
|
Sign up to set email alerts
|

A 3D stereo camera system for precisely positioning animals in space and time

Abstract: Here, we describe a portable stereo camera system that integrates a GPS receiver, an attitude sensor and 3D stereo photogrammetry to rapidly estimate the position of multiple animals in space and time. We demonstrate the performance of the system during a field test by simultaneously tracking the individual positions of six long-finned pilot whales, Globicephala melas. In shore-based accuracy trials, a system with a 50-cm stereo baseline had an average range estimation error of 0.09 m at a 5-m distance increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Despite the difficulties associated with observing wild delphinids, photogrammetry using unmanned aerial vehicles (Dawson et al, 2017 ; Scott & Perryman, 1991 ) or portable stereo photogrammetry systems (Howland et al, 2012 ; Macfarlane et al, 2015 ) offers feasible ways of measuring interindividual distances. It is necessary to consider, however, which interindividual distances to measure.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the difficulties associated with observing wild delphinids, photogrammetry using unmanned aerial vehicles (Dawson et al, 2017 ; Scott & Perryman, 1991 ) or portable stereo photogrammetry systems (Howland et al, 2012 ; Macfarlane et al, 2015 ) offers feasible ways of measuring interindividual distances. It is necessary to consider, however, which interindividual distances to measure.…”
Section: Discussionmentioning
confidence: 99%
“…For example, static poses and positions of animals can be generated from image and video data, allowing individual tracking and/or pose estimation in a variety of complex and naturalistic environments [29][30][31] . Depth sensing, radio-frequency identification (RFID) tagging, and multiple camera setups have been used in conjunction with standard video data to track animals in social and physical environments in which occlusions regularly occur [32][33][34][35][36] . However, position and pose estimation can only partially describe behaviors that are defined by interactions between animals and their environments, such as construction behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Visual observation is a method that is often used for accurate tracking of marine mammals at the surface (e.g. using land-based theodolite tracking [ 23 ], boat-based focal follows [ 43 ], or stereo photogrammetry [ 100 ]), but a quantitative assessment of its accuracy, as presented in this study, is relatively uncommon. The visual accuracy tests with a floating buoy showed that the errors in range generally contributed most to the combined positional error from range and bearing observations, which is consistent with results from more extensive testing during transect line surveys [ 101 ].…”
Section: Discussionmentioning
confidence: 99%